DOP010 Activating PIK3CD mutations cause severe intestinal lymphonodular hyperplasia and an IBD-like phenotype. (16th January 2018) - Farachi, S; Werner, L; Konnikova, L; Rea, F; Vardi, I; Romeo, E; Barel, O; De Angelis, P; Dall'Oglio, L; Rechavi, G; Snapper, S; Somech, R; et al.
Abstract: Background: More than 50 different monogenic disorders causing intestinal inflammation have been identified in recent years. Activated phosphoinositide 3-kinase δ syndrome (APDS) is a recently described primary immunodeficiency resulting from PIK3CD and PIK3R1 mutations that manifests in the first years of life. Our aim was to characterise the gastrointestinal manifestations and immunological alterations of patients with APDS who presented with a severe IBD-like phenotype. Methods: Detailed immune work-up was performed in three patients with APDS (two with PIK3CD mutation and one with PIK3R1 mutation) who presented with very early-onset IBD (VEOIBD). Whole exome sequencing was completed to identify pathogenic variants. In a single patient and two healthy controls paired blood and intestinal immune cells were analysed by Mass CyTOF and high-throughput sequencing of the T- and B-cell receptor gene segments. Results: All patients manifested with recurrent sinopulmonary infections, bronchiectasis and splenomegaly, as well as chronic diarrhoea due to severe intestinal lympho-nodular hyperplasia (Figure 1) and an IBD-like phenotype in the first years of life. Two patients developed intestinal diffuse large B-cell lymphomas in adulthood. Immune work-up displayed T-cell lymphopenia and increased IgM levels. Whole exome sequencing identified deleterious genetic variants in PIK3CD or in PIK3R1. Mass CyTOF analysis showed a marked decrease in B cells in the intestine and blood accompanied with an increase in memory CD4 and CD8 T cells. Moreover, patient's circulating CD4 and CD8 T cells produced very high quantities of IFNγ and TNFα. Finally, marked alterations in the T and B cell receptor repertoire patterns were observed in these patients with expansion of specific clones in both the blood and intestine. Conclusions: APDS should be included in the differential diagnosis of VEOIBD, especially in patients with intestinal lympho-nodular hyperplasia. Given the profound proliferation in the gut and tendency to develop lymphomas these patients should be monitored closely. Novel PI3K inhibitors should be evaluated as a potential targeted therapeutic modality in these patients.